Philosophy 167: Class 5 - Part 2 - Galileo Galilei: Publications and Polemics. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Lists Galileo's three most important works, and discusses the role of polemics in science.; Opening line: "Galileo's publications. Three of the books listed up here and by any imaginable standards monuments of Western Civilization."; Duration: 9:39 minutes.; Segment: Class 5, Part 2.